Kredit Pemilikan Rumah di Bank Konvensional Dan Bank Syariah Dalam Perbandingan Mekanisme Risiko Dan Keuntungan Bagi Nasabah - Nugraha, Naufal Satria; B, Baidhowi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Home Ownership Credit (KPR) is one of the financing instruments offered by banks to help people own a home. In Indonesia, Home Ownership Credit (KPR) consists of conventional KPR with an interest system and sharia KPR based on contracts such as murabahah, musyarakah mutanaqisah (MMQ), and ijarah muntahia bittamlik (IMBT). This study uses a literature study method to compare the mechanisms, risks and benefits of the two KPR schemes. The results of the study show that conventional KPR is more flexible but susceptible to interest rate fluctuations, while sharia KPR is more transparent with price certainty but has a higher initial cost. The selection of a KPR scheme should be adjusted to the customer’s financial needs and preferences.